M*A*S*H. Season five [videorecording (DVD)] - Gelbart, Larry; Alda, Alan, 1936-; Farrell, Mike; Morgan, Harry, 1915-2011; Swit, Loretta; Linville, Larry, 1939-2000; Burghoff, Gary; Farr, Jamie, 1934-; Christopher, William, 1932-2016 (Twentieth Century Fox Home Entertainment, 2008)
Korea, 1950. They were a MASH (Mobile army surgical hospital) unit stationed three miles from the front, positioned to provide quick care to the troops. Although it sometimes felt as if the incoming wounded would never stop, the docs and nurses of the 4077 were always ready with a steady hand, a smile and a laugh, healing our soldiers in both body and soul, and offering a touch of home, and often hilarity, in a foreign land. Includes all 24 episodes.